Pengaruh Teknologi Pembelajaran Berbasis Canva Terhadap Kemandirian Belajar Siswa di UPTD SMP Negeri 1 Gunungsitoli Alo’oa T.P 2024/2025 - Restu Jaya Laoli; Wahyutra Adilman Telaumbanua; Arianto Lahagu; Yearning Harefa (Universitas Negeri Medan, 2025)
This study aims to determine the effect of Canva-based learning technology on student learning independence at the Technical Implementation Unit (UPTD) of SMP Negeri 1 Gunungsitoli Alo'oa. The background of this research is based on the importance of utilizing interactive digital media in the learning process to increase student motivation and responsibility for learning, especially in the current digital era. Canva, as a graphic design platform that is easy to access and use, is believed to be a learning medium that supports active student engagement and encourages independent learning. This study used a quantitative approach with a quasi-experimental method. The study sample consisted of eighth-grade students divided into experimental and control groups. The instruments used were a learning independence questionnaire and documentation of the learning process. Data analysis used a t-test to determine significant differences between the groups that used Canva and those that did not. The results of this study indicate a significant effect of Canva-based learning technology on student learning independence. Students who used Canva demonstrated higher levels of learning independence compared to those who did not use the tool. Therefore, Canva can be used as an effective alternative learning medium to enhance student learning independence.